2020
DOI: 10.36054/jict-ikmi.v19i1.127
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Kualitas Website Seleksi Masuk Mahasiswa Dengan Metode McCall

Abstract: The use of websites as a medium for disseminating information is a matter that is familiar in this era of digital technology. Telkom University which is a tertiary institution in Indonesia which often carries digital themes in its campus certainly does not want to be left behind in the use of websites as a medium for disseminating information and marketing for the community. This study aims to analyze the quality of the information system on the smb.telkomunivesity.ac.id New Student Selection website which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…McCall, Richards and Walter suggested that what affects the quality of the software is a certain factor or criteria (Dwilestari & Nuris, 2020). McCall's method is the oldest test model developed in 1996.…”
Section: Mccallmentioning
confidence: 99%
“…McCall, Richards and Walter suggested that what affects the quality of the software is a certain factor or criteria (Dwilestari & Nuris, 2020). McCall's method is the oldest test model developed in 1996.…”
Section: Mccallmentioning
confidence: 99%